2015
DOI: 10.1177/1526602815619409
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Studies Evaluating the Effect of Cilostazol on Major Outcomes After Carotid Stenting

Abstract: Purpose: To evaluate the effect of cilostazol on major outcomes after carotid artery stenting (CAS). Methods: A systematic literature review was conducted conforming to established criteria in order to identify articles published prior to May 2015 evaluating major post-CAS outcomes in patients treated with cilostazol vs patients not treated with cilostazol. Major outcomes included in-stent restenosis (ISR) within the observation period, the revascularization rate, major/minor bleeding, and the myocardial infar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…A recent meta-analysis with a systemic review of clinical studiesdthat evaluated the effects of a cilostazol treatment after a carotid stent implantation for the treatment of asymptomatic or symptomatic stenosisdincluded 7 controlled trials (only 1 randomized trial) for a total of 1,297 patients. 12 Meta-analysis results showed a significantly lower in-stent restenosis rate in the patients treated with cilostazol after a mean 20-month follow-up: risk À85%, P < 0.001. Instead, the pooled incidence of infarction, stroke, and death at 1-and 20-month follow-up suggests a statistically not significant risk reduction of 28% and 24% for the cilostazol group, respectively.…”
Section: Carotid Revascularizationmentioning
confidence: 92%
“…A recent meta-analysis with a systemic review of clinical studiesdthat evaluated the effects of a cilostazol treatment after a carotid stent implantation for the treatment of asymptomatic or symptomatic stenosisdincluded 7 controlled trials (only 1 randomized trial) for a total of 1,297 patients. 12 Meta-analysis results showed a significantly lower in-stent restenosis rate in the patients treated with cilostazol after a mean 20-month follow-up: risk À85%, P < 0.001. Instead, the pooled incidence of infarction, stroke, and death at 1-and 20-month follow-up suggests a statistically not significant risk reduction of 28% and 24% for the cilostazol group, respectively.…”
Section: Carotid Revascularizationmentioning
confidence: 92%
“…Similarly, a study in patients with ischemic stroke or carotid artery stenting reported a significantly lower PRU (113.3 vs 170.2, p=0.021) and higher percentage platelet inhibition (64.9% vs 41.7%, p=0.005) in patients receiving cilostazol in combination with clopidogrel compared with clopidogrel monotherapy, respectively . A meta‐analysis found that cilostazol, either as monotherapy or in combination antiplatelet therapy in patients undergoing carotid artery stenting, was associated with a lower in‐stent restenosis rate compared with regimens without cilostazol; however, no significant difference was found in composite rates of myocardial infarction, stroke, or death . In patients with acute myocardial infarction undergoing coronary stenting in Korea, compared with a high‐dose clopidogrel regimen (clopidogrel 150 mg/day plus aspirin 200 mg/day), triple antiplatelet therapy (clopidogrel 75 mg/day plus aspirin 200 mg/day plus cilostazol 100 mg twice/day) resulted in a nonsignificant decrease in P2Y12 PRU (184.5 vs 131.5, p=0.085) and a significant increase in percentage platelet inhibition (42.5% vs 55.0%, p=0.034), respectively .…”
Section: Additional Antiplatelet Agentsmentioning
confidence: 96%
“…45 A meta-analysis found that cilostazol, either as monotherapy or in combination antiplatelet therapy in patients undergoing carotid artery stenting, was associated with a lower in-stent restenosis rate compared with regimens without cilostazol; however, no significant difference was found in composite rates of myocardial infarction, stroke, or death. 46 In patients with acute myocardial infarction undergoing coronary stenting in Korea, compared with a high-dose clopidogrel regimen (clopidogrel 150 mg/day plus aspirin 200 mg/day), triple antiplatelet therapy (clopidogrel 75 mg/day plus aspirin 200 mg/day plus cilostazol 100 mg twice/day) resulted in a nonsignificant decrease in P2Y12 PRU (184.5 vs 131.5, p=0.085) and a significant increase in percentage platelet inhibition (42.5% vs 55.0%, p=0.034), respectively. 47 Baseline clopidogrel hyporesponsiveness was not reported in this study.…”
Section: Cilostazolmentioning
confidence: 99%
“…A recent meta-analysis involving 1233 patients also indicated that cilostazol treatment was associated with a significantly lower ISR incidence after CAS during a mean follow-up of 20 months. 92 Authors concluded that cilostazol may decrease the ISR rates after CAS without affecting the risk of cardiovascular events and death, in both early and late settings.…”
Section: Treatment Of Irs After Casmentioning
confidence: 99%